Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/978-1-4614-0887-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Klotho and Chronic Kidney Disease

Abstract: Soluble Klotho (sKl) in the circulation can be generated directly by alterative splicing of the Klotho transcript or the extracellular domain of membrane Klotho can be released from membrane-anchored Klotho on the cell surface. Unlike membrane Klotho which functions as a coreceptor for fibroblast growth factor-23 (FGF23), sKl, acts as hormonal factor and plays important roles in anti-aging, anti-oxidation, modulation of ion transport, and Wnt signaling. Emerging evidence reveals that Klotho deficiency is an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 229 publications
(324 reference statements)
3
106
0
2
Order By: Relevance
“…This is in agreement with Hu et al, [51] as they reported that oral administration of antioxidant (troglitazone: antidiabetic with antioxidant properties) for 10 weeks significantly upregulates renal Klotho mRNA expression in OLETF rats. Cheng et al, [52] also reported that the reduced expression of klotho in cultured renal tubular cells of Streptozotocin-induced diabetic rats was reversed by antioxidant (Tiron).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with Hu et al, [51] as they reported that oral administration of antioxidant (troglitazone: antidiabetic with antioxidant properties) for 10 weeks significantly upregulates renal Klotho mRNA expression in OLETF rats. Cheng et al, [52] also reported that the reduced expression of klotho in cultured renal tubular cells of Streptozotocin-induced diabetic rats was reversed by antioxidant (Tiron).…”
Section: Discussionsupporting
confidence: 92%
“…Cheng et al, [52] also reported that the reduced expression of klotho in cultured renal tubular cells of Streptozotocin-induced diabetic rats was reversed by antioxidant (Tiron). Hu et al 2012 [51] proposed that overexpression of PPAR-γ (Peroxisome proliferator-activated receptor gamma) can be the underlying mechanism of increased renal Klotho expression by Antioxidant. The last step was to study the effect of combined exercise training with vitamin E treatment for 8 weeks on HFD induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble a-klotho, which is derived from the proteolytic cleavage of the extracellular portion of the membrane-bound a-klotho, can be measured in blood, urine, and cerebrospinal fluid. Alternatively, soluble aklotho can be generated directly by the alternative splicing of the a-klotho transcript [11]. Soluble Klotho protein functions as paracrine or autocrine hormones, modulating positive interactions by FGF23, including anti-aging, insulin-like growth factors, and the suppression of PTH.…”
Section: Klotho Klotho Protein and Its Functionmentioning
confidence: 99%
“…The main function of transmembrane Klotho is as a coreceptor for fibroblast growth factor-23, however, sKlotho appears to have several paracrine and endocrine functions, including modulation of ion transport, Wnt signal transduction, antirenin-angiotensin system, antisenescence, and antioxidation. 43 Human patients with CKD in general exhibit reduced renal expression of Klotho, 44 as well as reductions in sKlotho. In an apparent controversy, a recent study demonstrated that plasma and urinary levels of sKlotho are significantly elevated in patients with type 2 diabetes and preserved renal function.…”
Section: Vegf-a 165 Bmentioning
confidence: 99%